PENGOLAHAN BUAH MANGROVE MENJADI PRODUK MAKANAN DAN MINUMAN PADA KELOMPOK MASYARAKAT YAYASAN LINGKUNGAN HIDUP ESTUARI DESA CEMARA WETAN KABUPATEN INDRAMAYU - Mutiara Salsabiela; Asep Andri Astriyandi; Ira Puspita Windiari; Shaicfah Bachaer Nebu Nasukha; Randi Wijaya (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
The mangrove ecosystem in Cemara Wetan Village, Cantigi District, Indramayu Regency, has high potential but has not been optimally utilized, especially in economic aspects. Local communities still do not understand the added value of mangroves as raw materials for food products. Community service activities were carried out in the form of training on processing mangrove fruit into food and beverage products with economic value. The implementation method included a learning-by-doing approach, interactive discussions, and direct practice consisting of three main stages: preparation, implementation, and evaluation. This activity upholds the principle of CAPACITY (Involvement, Accessibility, Participation, Nodes, Innovation, Follow-up, and Direct Application) to ensure active community involvement. The training resulted in various processed products, such as dodol (sweet candy), syrup, wrakas leaf chips, and sponge cakes made from mangrove fruit, which have been simply packaged ready for marketing. The implementation results showed a 100% participant participation rate, with high enthusiasm during both theory and practice sessions. Participants actively asked questions, discussed, and were directly involved in the entire processing process. Positive feedback was also obtained, indicating a good acceptance of this innovation. This training has successfully increased the community's capacity to utilize local resources sustainably and opened up opportunities for developing ecotourism and mangrove-based creative economic businesses.